Wave-absorbing heating composite material, asphalt composite coiled material and asphalt coiled material laying method
By using a wave-absorbing heating composite material of discharge materials with an aspect ratio of greater than or equal to 5 in the asphalt roll, microwave-induced discharge is used to generate high-temperature plasma, the problem of low heating efficiency of asphalt rolls in the prior art is solved, and the effect of efficient heating and rapid bonding is achieved.
Patent Information
- Application Number
- CN202411666371.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art uses microwave heating asphalt coils, and the heating efficiency is low, especially in the construction of road asphalt and cement board bases, which is difficult to meet the demand for high heating rates.
A wave-absorbing heating composite material is used, which consists of discharge material and dielectric material. The length-diameter ratio of the discharge material is greater than or equal to 5. The diameter of the dielectric material and the length ratio of the discharge material is within the range of 0.5≤d dielectric/L discharge≤2.5. The discharge of the discharge material is induced by microwaves to generate high-temperature plasma, achieving efficient heating of the asphalt coil.
It significantly improves the microwave heating efficiency of asphalt rolls, meets the high heating rate requirements of asphalt rolls during the construction of the base surfaces such as cement boards, and realizes the rapid bonding and waterproofing functions of asphalt rolls.
Smart Images

Figure BDA0005144662110000121 
Figure BDA0005144662110000151 
Figure HDA0005144662120000011
Abstract
Description
Technical Field
[0001] The present invention relates to a wave-absorbing and heat-generating material, in particular to a wave-absorbing and heat-generating material used in the field of asphalt waterproofing coiled material laying, and more particularly to a wave-absorbing and heat-generating composite material, an asphalt composite coiled material and an asphalt coiled material laying method. Background Art
[0002] Asphalt rolls (such as asphalt waterproofing rolls) can be divided into hot-adhesive rolls and cold self-adhesive rolls according to whether they need to be heated during construction. Among them, hot-adhesive rolls have better bonding reliability and therefore have a higher market share. At present, hot-adhesive rolls are mainly heated by open flames to achieve thermal bonding, while hot-melt construction without open flames is more in line with green, low-carbon, and safe construction requirements, and therefore has received more and more attention.
[0003] Heating without open flames usually includes hot air heating, infrared heating, microwave heating and other heating methods. Among them, microwave heating does not rely on medium transmission, has a certain penetration, and has a heating effect only on specific absorbing fillers. It has the following advantages: (1) It can achieve precise heating of specific parts, avoiding asphalt aging in non-heating areas; (2) The roll can be heated after being laid flat without turning it over, which facilitates construction and improves efficiency. Therefore, microwave heating has more advantages in the field of asphalt roll laying.
[0004] However, there is a common problem of low heating efficiency when heating asphalt by microwave. For example, for microwave heating of road asphalt, it usually takes 10-12 minutes to heat the asphalt pavement to 130-160°C, which is slow to heat and has low heating efficiency.
[0005] At present, for asphalt mixtures such as road asphalt, absorbing fillers are mainly added therein to improve their microwave absorption efficiency and thus improve the heating efficiency. Commonly used absorbing fillers are conductive materials or magnetic materials. For example, patent documents CN111499268B, CN114426413B, CN114835438A, and CN115286290A respectively disclose the introduction of absorbing fillers into road asphalt mixtures or asphalt concrete, but the effect of improving the heating rate of the asphalt mixture is limited (the heating rate is generally around 0.3°C / s to 0.6°C / s).
[0006] In addition, asphalt rolls (asphalt waterproofing rolls) used for waterproofing of base layers such as cement boards are usually in sheet form. During construction, the asphalt rolls are usually laid on the surface (base surface) of the cement base. If microwaves are used as a heating source, the microwaves act on the asphalt rolls, causing the asphalt rolls to melt and bond to the base. The asphalt waterproofing rolls have a heating rate requirement much higher than that of road asphalt during the laying process, in order to meet the waterproofing construction period requirements and ensure the waterproofing function of the asphalt waterproofing rolls. Therefore, how to improve the microwave heating efficiency of asphalt waterproofing rolls during construction is still a technical problem that needs to be solved in this field. Summary of the invention
[0007] The present invention provides a microwave-absorbing and heating composite material, an asphalt composite coiled material and an asphalt coiled material laying method, which can improve the microwave heating efficiency of the coiled material during the construction process and effectively overcome the defects of the prior art.
[0008] One aspect of the present invention provides a microwave-absorbing and heat-generating composite material, comprising a discharge material and a dielectric material, wherein the aspect ratio of the discharge material is greater than or equal to 5.
[0009] According to an embodiment of the present invention, the aspect ratio of the discharge material is 10-20.
[0010] According to an embodiment of the present invention, the length of the discharge material is 0.2 mm to 2 mm.
[0011] According to one embodiment of the present invention, the diameter d of the dielectric material 介 The length L of the discharge material 放 The ratio of d 介 / L 放 Satisfy 0.5≤d 介 / L 放 ≤2.5.
[0012] According to an embodiment of the present invention, the diameter of the dielectric material is greater than or equal to the length of the discharge material.
[0013] According to one embodiment of the present invention, the electrical conductivity of the discharge material is greater than or equal to 10 S / m.
[0014] According to one embodiment of the present invention, the mass ratio of the dielectric material to the discharge material is (2-10):1; and / or the discharge material includes one or more of metal materials and metal oxides, and the metal materials include metal element materials and / or alloy materials; and / or, in the wave-absorbing and heat-generating composite material, the mass percentage of the discharge material is 8%-33%; and / or, the dielectric material contains silicon dioxide, and the mass percentage of the silicon dioxide in the dielectric material is greater than or equal to 50%; and / or, the dielectric material includes quartz sand and / or glass beads; and / or, in the wave-absorbing and heat-generating composite material, the mass percentage of the dielectric material is 40%-90%.
[0015] According to one embodiment of the present invention, the microwave-absorbing and heat-generating composite material further comprises a reinforcing material, and the reinforcing material comprises one or more of a magnetic material, a carbon-based material, and a conductive polymer, wherein:
[0016] The magnetic material includes one or more of iron sand, magnetic ore powder, ferrite powder, ferroferric oxide, steel slag and other magnetic materials containing at least one of iron, cobalt and nickel; and / or, the mass ratio of the reinforcing material to the discharge material is (0-2):1; and / or, in the wave-absorbing and heat-generating composite material, the mass percentage of the reinforcing material is 0-40%.
[0017] Another aspect of the present invention provides a method for laying asphalt roll material, comprising the following steps: laying a wave-absorbing and heat-generating material on one side surface of the asphalt roll material to obtain an asphalt roll material with a wave-absorbing and heat-generating layer; wherein the wave-absorbing and heat-generating material comprises the wave-absorbing and heat-generating composite material according to any one of claims 1 to 8; laying the asphalt roll material with the wave-absorbing and heat-generating layer on a base surface with the wave-absorbing and heat-generating layer facing the base surface, and then applying microwaves to the asphalt roll material with the wave-absorbing and heat-generating layer from the side of the asphalt roll material with the wave-absorbing and heat-generating layer away from the base surface, so that the asphalt roll material in the asphalt roll material with the wave-absorbing and heat-generating layer is melted and bonded to the base surface.
[0018] Another aspect of the present invention provides an asphalt composite roll material, comprising an asphalt roll material layer, and a wave-absorbing and heat-generating layer arranged on one side of the asphalt roll material layer, wherein the wave-absorbing and heat-generating layer comprises the above-mentioned wave-absorbing and heat-generating composite material.
[0019] The wave-absorbing and heating composite material, asphalt composite coil and asphalt coil laying method provided by the present invention adopt discharge material and dielectric material at the same time, and the aspect ratio of the discharge material is greater than or equal to 5. In such a wave-absorbing and heating composite material system, the discharge material is slender, and the discharge material can be induced to discharge by microwaves, and the air is broken down to generate high-temperature plasma, thereby generating heat through the discharge of the discharge material to achieve the heating effect of the asphalt coil. At the same time, the dielectric material can reduce the situation where the discharge materials contact each other and the charge cannot be concentrated and then cannot be discharged, thereby ensuring the discharge efficiency of the discharge material, and then ensuring the generation efficiency of the high-temperature plasma. At the same time, the dielectric material can also transfer the heat generated by the discharge of the discharge material to the asphalt, so that the asphalt coil absorbs heat and melts, and achieves the heating effect of the asphalt coil. Therefore, the wave-absorbing and heating composite material of the present invention can significantly improve the microwave heating efficiency of the asphalt coil, meet the heating rate requirements during the construction process of laying the asphalt coil on the surface (base surface) of the base layer such as cement board, realize the bonding of the asphalt coil to the base surface, and ensure the waterproof function of the asphalt coil. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of discharge materials overlapping and being blocked by dielectric materials;
[0021] Figure 2 This is a schematic diagram of the laying process of asphalt membrane;
[0022] Figure 3 This is a curve diagram showing the change of the temperature rise of the sand surface after heating for 10 seconds with the mass ratio of quartz sand SYS and steel wool fiber GM (m(SYS) / m(GM));
[0023] Figure 4 The bar graph is the relationship between the temperature rise of the sand surface after 10s heating and the particle size of the quartz sand SYS;
[0024] Figure 5 Fluorescence microscope photos of the composite sand of Example 2 and Example 6.
[0025] Explanation of reference numerals: 101: discharge material; 102: dielectric material; 2: asphalt roll material; 201: functional surface; 3: base layer; 30: base surface. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0027] An embodiment of the present invention provides a wave-absorbing and heat-generating composite material, comprising a discharge material and a dielectric material, wherein the aspect ratio of the discharge material is greater than or equal to 5.
[0028] According to the inventor's research, discharge material and dielectric material are simultaneously introduced into the microwave-absorbing and heat-generating composite material, and the aspect ratio of the discharge material is made greater than or equal to 5. Under such a composition system, the discharge material has a larger aspect ratio, which is conducive to the discharge material having a sharper end face. The sharp end face is easy to accumulate charge under the microwave electric field, achieving a high electric field strength, thereby realizing tip discharge, and then breaking through the air to generate high-temperature plasma, achieving the heating effect on the asphalt roll.
[0029] Among them, the dielectric material can block the discharge material and reduce the situation where the discharge material contacts each other and causes charge neutralization and inability to discharge, thereby ensuring the discharge efficiency of the discharge material and further ensuring the efficiency of high-temperature plasma generation. While blocking the discharge material, the dielectric material can also maintain a larger air gap in the wave-absorbing and heat-generating composite material, which is beneficial to the efficiency of high-temperature plasma generation generated by the discharge material discharging through the air, thereby improving the heating effect on the asphalt coil. At the same time, the dielectric material can also transfer the heat generated by the discharge of the discharge material to the asphalt, causing the asphalt coil to absorb heat and melt, thereby achieving a heating effect on the asphalt coil.
[0030] Therefore, the embodiments of the present invention can significantly improve the heat absorption and heating efficiency of the asphalt roll material, meet the heating rate requirements during the construction process of laying the asphalt roll material (asphalt waterproofing roll material) on the base surface (base surface) such as cement board, realize the bonding of the asphalt roll material to the base surface, and ensure the waterproof function of the asphalt roll material, thereby achieving the hot melt construction effect of the asphalt roll material.
[0031] Illustratively, the aspect ratio of the discharge material may be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range consisting of any two thereof.
[0032] In some embodiments, the aspect ratio of the discharge material can be 10 to 20, which is conducive to further improving the microwave heating efficiency of the asphalt coil during the laying construction process. The reason for this is that the discharge material has an aspect ratio of not less than 10, has a better tip effect, is conducive to achieving tip discharge efficiency under microwave induction, improves the generation efficiency of high-temperature plasma, and thus improves the microwave heating efficiency of the asphalt coil. At the same time, the discharge material has an aspect ratio of not more than 20, which can avoid problems such as mutual entanglement between the discharge materials, is conducive to industrial application, and is convenient for the uniform dispersion of components such as the discharge material in the microwave-absorbing and heat-generating composite material, is conducive to isolating more discharge materials through dielectric materials, reduces the contact between the discharge materials, and the resulting charge neutralization and inability to discharge. The discharge material has a smaller aspect ratio, which is conducive to the microwave-absorbing and heat-generating composite material containing a larger number of discharge materials (under the conditions of equal mass and length, the larger the aspect ratio of the discharge material and the finer the material, the greater the number of discharge materials), further ensuring the discharge efficiency. Therefore, by using a discharge material with an aspect ratio in the range of 10 to 20, it is conducive to more significantly improving the microwave heating efficiency of the asphalt coil during the laying construction process.
[0033] In some embodiments, the length of the discharge material can be 0.2mm to 2mm, for example, 0.2mm, 0.5mm, 0.8mm, 1mm, 1.3mm, 1.5mm, 1.8mm, 2mm or a range composed of any two of them, which is more conducive to the tip discharge of the discharge material under microwave induction, and makes the microwave-absorbing and heat-generating composite material contain a relatively large amount of discharge material, further improving the discharge efficiency, while maintaining the good dispersion of components such as the discharge material in the microwave-absorbing and heat-generating composite material, which is conducive to isolating more discharge materials through dielectric materials, reducing the contact between discharge materials and the resulting charge neutralization and inability to discharge, thereby further improving the microwave heating efficiency of the asphalt roll during the paving construction process.
[0034] Specifically, the discharge material is in the form of a thin and long fiber, and the aspect ratio of the discharge material is its length L 放 and diameter d 放 The ratio of (i.e. aspect ratio = L 放 / d 放 ), the length L of the discharge material can be measured by conventional methods in the art according to the embodiment of the present invention. 放 , diameter d 放 and aspect ratio, for example, by using a fluorescence microscope, it can be understood that the length L of the discharge material 放 , diameter d 放and aspect ratio respectively refer to average values. Taking the aspect ratio as an example, when testing the aspect ratio of a discharge material through a fluorescence microscope, the aspect ratios of multiple discharge materials (for example, at least 30 discharge material fibers) within the field of view can be tested, and then the average value is statistically calculated, which is the test result of the aspect ratio of the discharge material.
[0035] According to further research by the inventors, the diameter d of the dielectric material 介 The length L of the discharge material 放 The ratio of d 介 / L 放 Can satisfy 0.5≤d 介 / L 放 ≤2.5, which is more conducive to the size matching of dielectric material and discharge material. On the one hand, d 介 / L 放 Not less than 0.5, which can keep the size of dielectric materials relatively large, better block the mutual contact between discharge materials, reduce the problem of charge neutralization and loss of discharge effect caused by overlapping of discharge materials, thereby further improving the discharge efficiency of discharge materials. On the other hand, d 介 / L 放 Not more than 2.5, keeping the size of the dielectric material relatively small is conducive to maintaining an appropriate spacing between the discharge materials, so that there is a higher electric field strength between the discharge materials, which is more conducive to achieving tip discharge and further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0036] In some embodiments, the diameter of the dielectric material is greater than or equal to the length of the discharge material, which is more conducive to blocking the mutual contact between the discharge materials through the dielectric material, reducing the problem of charge neutralization and loss of discharge effect caused by overlapping of the discharge materials, thereby further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0037] Specifically, Figure 1 (a) does not contain dielectric material 102, and discharge materials 101 overlap each other; Figure 1 (b) contains dielectric material 102, the size of dielectric material 102 is relatively small, and it is relatively easy for discharge materials 101 to overlap ( Figure 1 (b) shows a schematic diagram of the overlapping of discharge materials 101, such as the overlapping parts shown by the curve with arrows); Figure 1 (c) contains dielectric material 102, which is relatively large in size and is more likely to block the mutual contact between the discharge materials 101 ( Figure 1 (c) shows a schematic diagram of the discharge material 101 being separated by the dielectric material 102, as shown by the overlapping parts of the curve with arrows). Figure 1If the discharge material 101 particles overlap each other, the current will flow directly between the overlapping discharge material 101 particles, so that discharge cannot be performed (such as Figure 1 (a) (no discharge, charge flows directly) and Figure 1 (b) (no discharge, direct charge flow)), so that it is impossible to break through the air to generate high-temperature plasma, and it is impossible to heat the asphalt coil; when the discharge material 101 is separated by the dielectric material 102, charge accumulation can be achieved (generally, charge accumulation is achieved at the end surface of the dielectric material 102), so that the discharge material 101 discharges and breaks through the air to generate high-temperature plasma (as shown in FIG. Figure 1 As shown in (c) (discharge, charge accumulation and breakdown), the distance △L between the two discharge materials 101 is greater than 0, and positive and negative charges accumulate at the ends of the discharge materials 101, discharge is achieved and the air is broken down to generate high-temperature plasma), thereby heating the asphalt coil. Therefore, by controlling the length of the dielectric material 102 to be greater than the length of the discharge material 101, it is more conducive to blocking the mutual contact between the discharge materials 101 through the dielectric material 102, thereby further improving the microwave heating efficiency of the asphalt coil during the laying construction process.
[0038] In some embodiments, the mass ratio of dielectric material to discharge material can be (2-10):1, for example 2:1, 3:1, 4:1, 4.5:1, 5:1, 5.5:1, 6:1, 6.5:1, 7:1, 7.5:1, 8:1, 9:1, 10:1 or a range composed of any two of them, which is beneficial for maintaining more discharge material while blocking the discharge material through dielectric material, reducing the problem of charge neutralization and inability to discharge caused by overlapping of discharge material, thereby further improving the discharge efficiency and improving the microwave heating efficiency of asphalt roll materials during the laying construction process.
[0039] In some embodiments, the mass percentage of the discharge material in the microwave-absorbing and heat-generating composite material can be 8% to 33%, for example, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33% or a range composed of any two of them. In this way, the content of the discharge material in the microwave-absorbing and heat-generating composite material is not less than 8%, which is conducive to ensuring a higher discharge efficiency. At the same time, the content of the discharge material is not higher than 33%, which is conducive to good dispersion of the discharge material and to the discharge material being blocked by the dielectric material, thereby reducing the contact between the discharge materials and the resulting problem of charge neutralization and inability to discharge, thereby further improving the discharge efficiency and improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0040] In some embodiments, the mass percentage of the dielectric material in the microwave-absorbing and heat-generating composite material can be 40% to 90%, for example, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or a range consisting of any two of them. This is beneficial for blocking the discharge material through the dielectric material, reducing the problem of charge neutralization and inability to discharge caused by overlapping of the discharge material, and improving the discharge efficiency. At the same time, it is beneficial for the dielectric material to conduct the heat generated by the discharge of the discharge material under the action of microwave induction to the asphalt roll, thereby further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0041] Specifically, the discharge material includes a conductive material, which can discharge under the induction of microwaves, thereby breaking through the air to generate high-temperature plasma, thereby heating the asphalt coil and improving the microwave heating efficiency.
[0042] In some embodiments, the electrical conductivity of the discharge material may be greater than or equal to 10S / m. By using a discharge material with an electrical conductivity greater than or equal to 10S / m, it is more conducive to the discharge of the discharge material under microwave induction, thereby further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0043] For example, the electrical conductivity of the discharge material may be greater than or equal to 3000 S / m, or greater than or equal to 5000 S / m, or greater than or equal to 8000 S / m, or greater than or equal to 10000 S / m, or greater than or equal to 30000 S / m, or greater than or equal to 50000 S / m, or greater than or equal to 80000 S / m, or greater than or equal to 100000 S / m, or greater than or equal to 130000 S / m, or greater than or equal to 150000 S / m, or greater than or equal to 180000 S / m, or greater than or equal to 200000 S / m, or greater than or equal to 226750 S / m. By using a discharge material with an electrical conductivity greater than or equal to 10 S / m, it is more conducive to the discharge of the discharge material under microwave induction, and the microwave heating efficiency of the asphalt coil during the paving construction process is further improved.
[0044] Specifically, the discharge material may include one or more of metal materials and metal oxides. The metal materials may include metal element materials and / or alloy materials. The metal oxides include, for example, iron oxide.
[0045] Specifically, the discharge material is in the form of elongated particles with an aspect ratio greater than or equal to 5, and can be specifically in the form of fibers, that is, the discharge material can include conductive material fibers containing the above-mentioned conductive material, for example, metal fibers containing the above-mentioned metal material, and the metal fibers include, for example, steel wool fibers.
[0046] In some embodiments, the dielectric material contains silicon dioxide (SO2), and the mass percentage of silicon dioxide in the dielectric material is greater than or equal to 50%, and can further be greater than or equal to 67%, which is beneficial to further improve the microwave heating efficiency of the asphalt roll during the laying construction process. The reason is that the dielectric material has good insulation and thermal conductivity. On the one hand, the dielectric material has better isolation ability for the discharge material, which is more conducive to blocking the contact problem between the discharge materials, thereby improving the discharge efficiency. On the other hand, its good thermal conductivity can improve the efficiency of transferring the heat generated by the discharge material to the asphalt roll, thereby further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0047] Specifically, the dielectric material may include quartz sand and / or glass beads.
[0048] Generally, the mass percentage of silicon dioxide in high-purity quartz sand is greater than or equal to 95%, and can further be greater than or equal to 98%. The embodiment of the present invention can use conventional high-purity quartz sand in the field as a dielectric material, and there is no special limitation on this.
[0049] Generally, the mass percentage of silicon dioxide in glass microspheres can be greater than or equal to 50%. Glass microspheres are made of glass, are smooth and spherical, have low friction, and have good dispersibility when applied to microwave-absorbing and heating composite materials. The embodiments of the present invention can use conventional glass microspheres in the art as dielectric materials, without any special restrictions.
[0050] In the embodiments of the present invention, the materials such as the discharge material and the dielectric material used can be obtained by conventional methods to obtain materials that meet the characteristics such as preset length. For example, discharge materials that meet the characteristics such as preset aspect ratio and length can be commercially obtained. Alternatively, the length, particle size, aspect ratio and other characteristics of the discharge material and the dielectric material can also be regulated by conventional methods, and there is no particular limitation on this.
[0051] In addition, the above-mentioned microwave-absorbing and heat-generating composite material may or may not include reinforcing materials (or performance enhancing materials). When reinforcing materials are included, the heating performance of the microwave-absorbing and heat-generating composite material can be further enhanced, thereby improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0052] Specifically, the above-mentioned reinforcing materials may include one or more of carbon-based materials, conductive polymers, and magnetic materials, among which carbon-based materials and conductive polymers can be used as conductive performance enhancing materials. By introducing conductive performance enhancing materials, it is beneficial to further improve the discharge efficiency of the wave-absorbing and heat-generating composite material, thereby enhancing its heating performance and improving the microwave heating efficiency of the asphalt roll during the laying construction process; magnetic materials are used as magnetic performance enhancing materials. By introducing magnetic performance enhancing materials, in the process of applying microwaves to the wave-absorbing and heat-generating composite material, it is beneficial to further enhance the wave-absorbing and heating effect of the wave-absorbing and heat-generating composite material through microwave convergence, arc expansion, wave-absorbing and heating, etc., thereby further improving the microwave heating efficiency of the asphalt roll during the laying construction process.
[0053] Specifically, the carbon-based material may include one or more of graphene, graphite-based materials, and carbon black, and the graphite-based material may specifically include expanded graphite.
[0054] Specifically, the conductive polymer (intrinsic conductive polymer) may include one or more of polypyrrole, polyaniline, polythiophene, and polyacetylene.
[0055] Specifically, the magnetic material may include one or more of iron sand, magnetic ore powder, ferrite powder, ferroferric oxide, steel slag and other magnetic materials containing at least one of iron, cobalt and nickel. These materials can all be conventional magnetic materials, which can be commercially available or prepared by conventional methods in the art, and there is no particular limitation on this.
[0056] In some embodiments, the mass ratio of the enhancement material to the discharge material is (0-2):1, for example, 0, 0.1:1, 0.3:1, 0.5:1, 0.7:1, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1 or a range consisting of any two thereof.
[0057] In some embodiments, the mass percentage of the reinforcing material in the wave-absorbing and heat-generating composite material can be 0-40%, for example, 0 (i.e., no reinforcing material is added to the wave-absorbing and heat-generating composite material), 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range consisting of any two of them.
[0058] In a specific implementation, the discharge material and the dielectric material (or isolation material) can be mixed, stirred and dispersed evenly to obtain a wave-absorbing and heat-generating composite material (or wave-absorbing and heat-generating composite sand or compound sand); wherein, when the wave-absorbing and heat-generating composite material includes a reinforcing material (or performance enhancing material), after the discharge material and the dielectric material are mixed and stirred and dispersed evenly, the reinforcing material is added thereto, and then stirred and dispersed evenly to obtain the wave-absorbing and heat-generating composite material.
[0059] In the embodiment of the present invention, the microwave-absorbing and heat-generating composite material can be applied to the laying process of laying asphalt coiled material on the surface of a base layer such as a cement board. Under the action of microwaves, the discharge material in the microwave-absorbing and heat-generating composite material generates heat by discharging, so that the surface of the asphalt coiled material facing the base layer is melted, and then bonded to the base layer, thereby forming an asphalt composite coiled material on the surface (base surface) of the base layer. By using the above-mentioned microwave-absorbing and heat-generating composite material, the microwave heating efficiency of the asphalt coiled material during the construction process can be significantly improved.
[0060] The embodiment of the present invention also provides a method for laying asphalt coiled material, comprising the following steps: laying a wave-absorbing and heating material on one side surface (first side) of the asphalt coiled material to form a wave-absorbing and heating layer to obtain an asphalt coiled material with a wave-absorbing and heating layer; laying the asphalt coiled material with the wave-absorbing and heating layer on a base surface, with the wave-absorbing and heating layer facing the base surface, and then applying microwaves to the asphalt coiled material with the wave-absorbing and heating layer from the side of the asphalt coiled material with the wave-absorbing and heating layer away from the base surface, so that the asphalt coiled material in the asphalt coiled material with the wave-absorbing and heating layer is melted and adhered to the base surface. The wave-absorbing and heating material includes the above-mentioned wave-absorbing and heating composite material.
[0061] In specific implementation, the asphalt coil 2 can be heated to make it sticky, and then the wave-absorbing and heat-generating composite material is evenly spread on the functional surface 201 of the asphalt coil 2 (i.e., the first surface of the asphalt coil 2 for bonding to the base layer 3). After roller compaction, the attached sand (i.e., the wave-absorbing and heat-generating composite material not adhered to the asphalt coil 2) is removed to form a wave-absorbing and heat-generating layer covering the functional surface 201 of the asphalt coil 2 (formed by the wave-absorbing and heat-generating composite material adhered to the functional surface 201 of the asphalt coil 2). After cooling, an asphalt coil with a wave-absorbing and heat-generating layer (i.e., an asphalt coil with a wave-absorbing and heat-generating sandy surface) 2 is obtained. The side of the asphalt coil with the wave-absorbing and heat-generating layer is usually called the bottom of the asphalt coil, i.e., the bottom of the asphalt coil obtained is sandy. The asphalt coil 2 can be heated in a heating device such as an oven. The heating temperature can be 70-90°C, for example, 80°C, and the heating time can be 8min-12min, for example, 10min, so that the asphalt coil has stickiness.
[0062] Subsequently, microwaves may be applied to the other side surface (i.e., the second side, such as the functional surface 201) of the asphalt coiled material 2. Figure 2 (a) to (d)), so that the discharge material 101 in the microwave-absorbing and heat-generating composite material discharges under the action of microwaves (such as Figure 2 (b) and (c) of FIG. 1 ), the air is broken down to generate high temperature plasma, thereby heating the asphalt coil 2 (as shown in FIG. Figure 2 (c)), so that the side of the asphalt coil 2 facing the base 3 melts and then adheres to the base 3 (as shown in FIG. Figure 2 As shown in (d), it can be bonded to the base layer 3 under rolling. Figure 2 As shown in (d), the asphalt composite roll bonded to the base surface 30 includes an asphalt roll layer formed by an asphalt roll 2, and a wave-absorbing and heat-generating layer arranged on one side of the asphalt roll layer, the wave-absorbing and heat-generating layer includes a wave-absorbing and heat-generating composite material, and the wave-absorbing and heat-generating composite material is located on the side of the asphalt roll layer facing the base layer 3 and embedded in the asphalt roll layer 2 (that is, the asphalt composite roll is an asphalt roll with a wave-absorbing and heat-generating layer on the bottom).
[0063] In the embodiment of the present invention, microwaves may be applied to the microwave-absorbing coiled material by a conventional microwave application method, and there is no particular limitation to this.
[0064] In the embodiment of the present invention, the asphalt membrane may be a conventional asphalt waterproof membrane in the art, such as an SBS modified asphalt waterproof membrane, etc., and there is no particular limitation on this.
[0065] An embodiment of the present invention further provides an asphalt composite coil, comprising an asphalt coil layer and a wave-absorbing and heat-generating layer disposed on one side of the asphalt coil layer, wherein the wave-absorbing and heat-generating layer comprises the above-mentioned wave-absorbing and heat-generating composite material.
[0066] In the embodiment of the present invention, the wave-absorbing and heat-generating material can be laid on one surface of the asphalt roll material in accordance with the aforementioned method to form a wave-absorbing and heat-generating layer to obtain an asphalt composite roll material (i.e., an asphalt roll material with a wave-absorbing and heat-generating layer), and the asphalt composite roll material can be laid on the base surface in accordance with the aforementioned method to melt the asphalt roll material in the asphalt roll material with the wave-absorbing and heat-generating layer and bond to the base surface, thereby bonding the asphalt composite roll material to the base surface, which will not be elaborated in detail.
[0067] Specifically, the above-mentioned asphalt composite roll material can be an asphalt composite roll material bonded to the surface of a base layer such as a cement board, and can be formed on the surface of the base layer by the above-mentioned asphalt roll material laying method, which will not be described in detail.
[0068] The present invention is further described below by means of specific examples. In the following examples and comparative examples, the length L of the discharge material 放 , diameter d 放 The aspect ratio, diameter of dielectric material and diameter of reinforcing material are measured by fluorescence microscope. When testing each parameter, 50 material particles are tested to obtain 50 test values, and the average value of the 50 test values is taken as the final test result. Taking the aspect ratio of discharge material as an example, when testing by fluorescence microscope, the aspect ratio of 50 discharge materials (such as steel wool fibers) is tested (the length L is measured respectively). 放 and diameter d 放 , according to the aspect ratio = L 放 / d 放 The aspect ratio is calculated), and then the average value is calculated to obtain the aspect ratio of the discharge material.
[0069] In the following examples and comparative examples, the asphalt roll used is an SBS modified asphalt roll with a thickness of 4 mm, and its bottom (lower surface) covering material is a polyethylene film (PE film). The SBS modified asphalt roll is Oriental Yuhong PMB741 II type 4 mm elastomer modified asphalt roll.
[0070] In the following examples and comparative examples, unless otherwise specified, the electrical conductivity of the steel wool fiber used is greater than 10 S / m (approximately 226750 S / m), and its composition is shown in Table 1.
[0071] In the following examples and comparative examples, the composition of the steel slag, the composition of the quartz sand, and the composition of the glass beads are shown in Table 1, respectively.
[0072] Table 1 Composition of steel wool fiber, quartz sand and glass beads
[0073]
[0074] Example 1
[0075] The composite sand (wave absorbing and heating composite material) provided in Example 1 is prepared by mixing steel wool fiber (GM) and quartz sand (SYS) in a mass ratio of 1:2.5; wherein the steel wool fiber has a fiber length L 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, and the average diameter is about 0.6mm.
[0076] Example 2
[0077] The composite sand provided in Example 2 is prepared by mixing steel wool fiber and quartz sand in a mass ratio of 1:5; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, and the average diameter is about 0.6mm.
[0078] Example 3
[0079] The composite sand provided in Example 3 is prepared by mixing steel wool fiber and quartz sand in a mass ratio of 1:7.5; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, and the average diameter is about 0.6mm.
[0080] Example 4
[0081] The composite sand provided in Example 4 is prepared by mixing steel wool fiber and quartz sand in a mass ratio of 1:10; wherein the fiber length L of the steel wool fiber is 放About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, and the average diameter is about 0.6mm.
[0082] Example 5
[0083] The composite sand provided in Example 5 is prepared by mixing steel wool fiber and quartz sand in a mass ratio of 1:5; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 10-20 mesh, and the average diameter is about 1.5mm.
[0084] Example 6
[0085] The composite sand provided in Example 6 is prepared by mixing steel wool fiber and quartz sand in a mass ratio of 1:5; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 40-50 mesh, and the average diameter is about 0.36mm.
[0086] Example 7
[0087] The composite sand provided in Example 7 is prepared by mixing steel wool fiber and glass beads (GB) in a mass ratio of 1:5; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 The particle size of the glass beads is about 0.045 mm, the particle size distribution of the glass beads is 20-40 mesh, and the average diameter is about 0.6 mm.
[0088] Example 8
[0089] The composite sand provided in Example 8 is prepared by mixing steel wool fiber, quartz sand, and expanded graphite (conductive performance enhancing material) in a mass ratio of 1:5:0.05; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放 It is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, the average diameter is about 0.6mm, and the particle size of expanded graphite (PMO325) is 325 mesh.
[0090] Example 9
[0091] The composite sand provided in Example 9 is prepared by mixing steel wool fiber, quartz sand and steel slag (GZ) in a mass ratio of 1:4:1; wherein the fiber length L of the steel wool fiber is 放 About 0.6 mm, diameter d 放The particle size of quartz sand is about 0.045mm, the particle size distribution of quartz sand is 20-40 mesh, the average diameter is about 0.6mm, and the particle size distribution of steel slag (magnetic performance enhancing material) is 20-40 mesh, the average diameter is about 0.6mm.
[0092] Embodiment 10: The difference from Embodiment 2 is that the aspect ratio L of the steel wool fiber used is 放 / d 放 The other conditions are the same as those in Example 2.
[0093] Comparative Example 1: The difference from Example 2 is that the aspect ratio L of the steel wool fiber used is 放 / d 放 The other conditions are the same as those in Example 2.
[0094] The composition of the microwave-absorbing and heat-generating composite materials in each embodiment and comparative example (the mass ratio of the discharge material, the dielectric material, and the reinforcing material), the length L of the discharge material 放 , the diameter of the discharge material d 放 , the aspect ratio L of the discharge material 放 / d 放 , the length of the dielectric material d 介 The length L of the discharge material 放 The ratio of d 介 / L 放 The conditions are summarized in Table 2.
[0095] In addition, the following microwave heating test was carried out using the composite sand of each embodiment and comparative example.
[0096] S1. Laying compound sand: remove the PE film on the lower surface of the SBS modified asphalt membrane to expose the modified asphalt on the lower surface, place it in an oven at 80°C and heat it for 10 minutes to make the modified asphalt on the lower surface sticky (i.e., make the functional surface of the asphalt membrane sticky), spread the compound sand evenly on the surface, compact it with a roller, and brush off the floating sand to obtain an asphalt membrane with a wave-absorbing and heat-generating sand surface (i.e., an asphalt membrane with a wave-absorbing and heat-generating sand surface).
[0097] S2. Wave absorption and heating performance test
[0098] In order to meet the demand for rapid construction of hot-melt membranes in actual construction applications, the temperature rise performance of the microwave-absorbing heating membrane (i.e., asphalt membrane with microwave-absorbing heating sand surface) heated in a household 700W microwave oven for 10s was tested. The test process is as follows: the asphalt membrane with microwave-absorbing heating sand surface (i.e., the membrane covered with compound sand) was cut into uniform specifications (size of 5cm×10cm), and then placed on the cement board with the microwave-absorbing heating sand surface facing the cement board, and placed in a 700W microwave oven for 10s; after heating, the membrane was taken out and the infrared temperature measurement of the microwave-absorbing heating sand surface was quickly performed within about 1s. The temperature rise results of the sand surface heated for 10s are shown in Table 2. Figure 3 and Figure 4 .
[0099] In addition, comparative example 2 was carried out with reference to the above process. The difference between comparative example 2 and embodiments 1 to 10 is that step S1 was not carried out, but the SBS modified asphalt coil was directly subjected to step S2, wherein after heating, the coil was taken out of the microwave oven, and the PE surface of the coil (i.e., the surface of the PE film at the bottom of the SBS modified asphalt coil) was quickly measured by infrared temperature within about 1 second. The results of the temperature rise of the sand surface after 10 seconds of heating are shown in Table 2. The temperature rise of the sand surface after 10 seconds of heating is the difference between the temperature measured by infrared temperature measurement (i.e., the temperature after 10 seconds of heating) and the temperature before heating (25°C).
[0100] Table 2 Composition and related parameters of microwave-absorbing and heat-generating composite materials
[0101]
[0102] It can be seen from Table 1 that, relative to Comparative Examples 1 and 2, Examples 1 to 10 can significantly improve the microwave heating efficiency of asphalt membranes by adopting composite sand including discharge materials and dielectric materials and using discharge materials with an aspect ratio greater than or equal to 5, meet the heating rate requirements during the construction process of laying asphalt membranes on base surfaces (base surfaces) such as cement boards, achieve bonding of the asphalt membranes to the base surface, and ensure the waterproof function of the asphalt membranes.
[0103] also, Figure 3 The temperature rise of the sand surface after 10s heating is plotted using the temperature rise data of Examples 1 to 4 as a function of the mass ratio of quartz sand to steel wool fiber (m(SYS) / m(GM)). Figure 3It can be seen that in the process of m(SYS) / m(GM increasing from 2.5 to 10, the temperature rise shows a trend of increasing first and then decreasing. The reason is that when the amount of quartz sand is small, the barrier effect on steel wool fiber is relatively weak. With the increase of the amount of quartz sand, the barrier effect of quartz sand on steel wool fiber can be improved, and the problem of overlapping of steel wool fibers and thus reducing the discharge efficiency can be reduced. When the amount of quartz sand is too large, the amount of steel wool fiber will be relatively reduced, which will also affect the discharge efficiency and thus affect the temperature rise effect.
[0104] also, Figure 4 The 10s heating sand surface temperature rise (10s sand surface temperature rise) and SYS particle size (diameter d 介 ) from Table 2 and Figure 4 It can be seen that within the range of SYS particle size from 0.36 mm to 1.5 mm, as the SYS particle size increases (d 介 / L 放 The reason for this is that when the size of the quartz sand is smaller than that of the steel wool fiber (d 介 / L 放 <1), the barrier effect of quartz sand on steel wool fiber is relatively weak, and when the size of quartz sand is comparable to that of steel wool fiber, or larger than that of steel wool fiber (d 介 / L 放 ≥1), which can improve the barrier effect of quartz sand on steel wool fibers and reduce the problem of overlapping of steel wool fibers and thus reducing the discharge efficiency. The composite sands of Example 2 and Example 6 were analyzed by fluorescence microscopy, and the fluorescence microscope photo of the composite sand of Example 2 (SYS (20-40 mesh) dispersion GM fluorescence microscope photo) was measured. Figure 5 (a), the fluorescence microscope photo of the composite sand of Example 6 (SYS (40-50 mesh) dispersed GM fluorescence microscope photo) see Figure 4 (b).
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A microwave-absorbing and heat-generating composite material, characterized in that: The invention comprises a discharge material and a dielectric material, wherein the aspect ratio of the discharge material is greater than or equal to 5.
2. The microwave-absorbing and heat-generating composite material according to claim 1, characterized in that: The aspect ratio of the discharge material is 10-20.
3. The microwave-absorbing and heat-generating composite material according to claim 1, characterized in that: The length of the discharge material is 0.2 mm to 2 mm.
4. The microwave-absorbing and heat-generating composite material according to claim 1, characterized in that: The diameter d of the dielectric material 介 The length L of the discharge material 放 The ratio d 介 / L 放 Satisfy 0.5≤d 介 / L 放 ≤2.
5.
5. The microwave-absorbing and heat-generating composite material according to any one of claims 1 to 4, characterized in that: The diameter of the dielectric material is greater than or equal to the length of the discharge material.
6. The microwave-absorbing and heat-generating composite material according to any one of claims 1 to 4, characterized in that: The electrical conductivity of the discharge material is greater than or equal to 10 S / m.
7. The microwave-absorbing and heat-generating composite material according to any one of claims 1 to 4, characterized in that: The mass ratio of the dielectric material to the discharge material is (2-10):1; And / or, the discharge material includes one or more of metal materials and metal oxides, and the metal materials include metal element materials and / or alloy materials; And / or, in the microwave-absorbing and heat-generating composite material, the mass percentage of the discharge material is 8% to 33%; And / or, the dielectric material contains silicon dioxide, and the mass percentage of the silicon dioxide in the dielectric material is greater than or equal to 50%; And / or, the dielectric material includes quartz sand and / or glass beads; And / or, in the microwave-absorbing and heat-generating composite material, the mass percentage of the dielectric material is 40% to 90%.
8. The microwave-absorbing and heat-generating composite material according to any one of claims 1 to 4, characterized in that: The wave-absorbing and heat-generating composite material further includes a reinforcing material, and the reinforcing material includes one or more of a magnetic material, a carbon-based material, and a conductive polymer, wherein: The magnetic material includes one or more of iron sand, magnetic ore powder, ferrite powder, ferroferric oxide, steel slag and other magnetic materials containing at least one of iron, cobalt and nickel; And / or, the mass ratio of the reinforcing material to the discharge material is (0-2):1; And / or, in the microwave-absorbing and heat-generating composite material, the mass percentage of the reinforcing material is 0-40%.
9. A method for laying asphalt coiled material, characterized in that: The following steps are involved: Laying a wave-absorbing and heat-generating material on one side of the asphalt coiled material to obtain an asphalt coiled material with a wave-absorbing and heat-generating layer; wherein the wave-absorbing and heat-generating material comprises the wave-absorbing and heat-generating composite material according to any one of claims 1 to 8; The asphalt roll material with the wave-absorbing and heat-generating layer is laid on a base surface with the wave-absorbing and heat-generating layer facing the base surface, and then microwaves are applied to the asphalt roll material with the wave-absorbing and heat-generating layer from the side of the asphalt roll material with the wave-absorbing and heat-generating layer facing away from the base surface, so that the asphalt roll material in the asphalt roll material with the wave-absorbing and heat-generating layer is melted and adhered to the base surface.
10. An asphalt composite coil, characterized in that: It comprises an asphalt coiled material layer and a wave-absorbing and heat-generating layer arranged on one side of the asphalt coiled material layer, wherein the wave-absorbing and heat-generating layer comprises the wave-absorbing and heat-generating composite material according to any one of claims 1 to 8.
Citation Information
Patent Citations
An asphalt mixture with improved microwave absorption efficiency and its preparation method
CN111499268B
Wave-absorbing asphalt mixture
CN114426413B
Cooling type pouring asphalt concrete capable of being heated by microwaves and preparation method of cooling type pouring asphalt concrete
CN114835438A
Wave-absorbing asphalt mixture capable of rapidly repairing asphalt pavement cracks and preparation method thereof
CN115286290A